MM/PB(GB)SA benchmarks on soluble proteins and membrane proteins - Wang, Shiyu; Sun, Xiaolin; Cui, Wenqiang; Yuan, Shuguang (Frontiers in Pharmacology, 2022)
Predicting protein-ligand binding free energy rapidly and accurately remains a challenging question in modern drug discovery. Molecular mechanics/Poisson-Boltzmann (Generalized Born) surface area (MM/PB(GB)SA) has emerged as an essential tool for accelerating cost-efficient binding free energy calculation. In this study, we present benchmarks with three membrane-bound protein systems and four soluble protein systems. Different parameters were sampled for different benchmarks to explore the highest accuracy, including ligand charges, protein force fields, extra points, GB models, nonpolar optimization methods, internal dielectric constants and membrane dielectric constants. Comparisons of accuracy were made between MM/PB(GB)SA, docking and free energy perturbation (FEP). The results reveal a competitive performance between MM/PB(GB)SA and FEP. In summary, MM/PB(GB)SA is a powerful approach to predict ligand binding free energy rapidly and accurately. Parameters of MM/PB(GB)SA calculations, such as the GB models and membrane dielectric constants, need to be optimized for different systems. This method can be served as a powerful tool for drug design.